Perilaku Geser pada Keadaan Layan dan Batas Balok Beton Bertulang Berlubang Memanjang - Krasna, Wiku A; Sulistyo, Djoko; Supriyadi, Bambang (Jurnal Semesta Teknika, 2010)
I cross-section of reinforced concrete reduces weight and concrete needs, but the reduction in strength is not considerably large. In addition, I section reinforced concrete beam is relatively complicated and takes much longer time for manufacturing. Another geometric cross-section which results in equivalent weight reduction with that of I cross-section concrete beam may be hollow square crosssections of reinforced concrete beams. This research was conducted to identify and compare the behavior of the shear and dynamic effects of hollow core reinforced concrete beam with an I cross-section beam that equivalent with its. The specimens being tested were four reinforced concrete beams, of 2000 mm length, consisted of a T beam with bottom flange as control beam (BK) possessing dimensions of bfa = 600 mm, bw = 125 mm, bfb = 200 mm, h = 300 mm, tf = 100 mm, and three hollow core T beams as tested beam (BB1, BB2 and BB3) possessing dimensions of bf = 600 mm, bw = 200 mm, blubang = 75 mm h = 300 mm, tf = 100 mm. Static loading was applied by means of a hydraulic jack in a four-point loading system, were. Dynamic loading test was carried out by vibrating the beams to obtain the natural frequency, where the vibrating load were produced by a mechanical vibrator. Whilst the data on the static load carrying capacity was recorded at the first crack and at each initial additional crack until the ultimate fracture, those on dynamic loading was recorded on the solid block, at the first crack and at yield. The parameters being used was the magnitude of deflection, strain of the reinforcing steel and concrete, crack pattern and natural frequency. It can be concluded that the hollow core reinforced concrete beam can be used as an alternative to I section reinforced concrete beam. It was noticed that the difference in shear load carrying capacity between control beam (BK) and hollow beam (BB) was not considerably significant, where the difference between BK (299.3 kN) and BB1 (337.6 kN) is 12.79%, that with BB2 (350, 6 kN) or 17.14%, and that with BB3 (289.4 kN) or â3.31%. The natural frequency of BK is 58.594 Hz, 15.769% larger than the natural frequency of BB3 with 49.354 Hz. The natural frequencies of tested beam decreased with the increased of damage to the beam.